The Degree Of Understanding Of Zakat On Profession/Income In Jepara Regency - Aan Zainul Anwar; Miftah Arifin (IAIN Manado, 2018)
This study aimed to determine the degree of understanding of zakat on profession/income and the characteristics of the community distribution model as an effective collection model for zakat institutions. This study used a qualitative method with 68 respondents from various professional work backgrounds including civil servants, teachers, employees, military, police, and government officials. The results of this study were that Jepara people have a high degree of understanding about zakat but have not been fully able to calculate nishab of zakat especially zakat on profession/income. Therefore, not all people who are obliged to pay zakat on professionand the distribution of zakat on professionis still directly to mustahiq.Keywords: Zakat on Profession/Income; Understanding of Zakat; Zakat; Alms